Diasporic transnationalism - Retis, Jessica (2024)
This conceptual trailer reflects on how the concepts of diaspora and transnationalism have served as prominent research lenses through which to observe contemporary migrations. While the term “diaspora” refers to a community or group and has been widely used in history and literary studies, concepts such as transnationalism – along with transnational spaces, fields, and formations – refer to processes that transcend international borders and thus seem to describe more abstract phenomena in the language of social sciences. This theoretical and conceptual framework can serve as a foundation for analyzing and understanding Latin American diasporic transnationalisms from a communication perspective as well.